Cognitive ability, self-understanding and personality - Bakračevič Vukman, Karin (Anthropos (Ljubljana), 2011)
This study investigates the relations between cognitive ability, self-understanding, and personality. That is, the study was designed to specify if reasoning ability in different domains and self-evaluation and self-representation in these domains are related to each of the Big Five factors of personality. The general assumption, which is suggested by a number of recent studies, is that there indeed are relations between these three distinct dimensions (i. e., cognition, self-understanding, and personality) of the person. This study aspires to further decipher and clarify these relations. The results revealed that personality is variably related to cognitive functioning and cognitive self-representations. Specifically, cognitive ability was significantly but weakly related to only two of the dimensions of personality, namely openness and conscientiousness. On the other hand, there was very high positive correlation between the general self-representation factor and openness to experience, and moderate correlations with extraversion, agreeableness and conscientiousness.
Keywords: kognicija; kognitivne sposobnosti; osebnost; psihologija; razvoj